Laura's star - Baumgart, Klaus; Waite, Judy (Wilton, CT : Tiger Tales, 2002)
After rescuing a fallen star, a young girl learns a lesson about friendship.
Originally published: Frankfurt, Germany : Baumhaus Verlag, 1996.
Stars made of reflective material attached to pages.
3.5
K-3
Keywords: Friendship -- Fiction; Stars -- Fiction; Friendship -- Fiction; Stars -- Fiction